Buya Hamka: Membangun Generasi Muhammadiyah dengan Ilmu Pengetahuan - Allefansyah Binta Pradikas; Revalyna Ayu Pradiva; Rahma Fauziyah Syifa’; Juwita Yayang Marga Cyntia; Satria Tegar Wijaya; Astika Nurul Hidayah (Universitas 45 Surabaya, 2024)
The famous Muhammadiyah figure, Buya Hamka, emphasized that the integration of religion and science is important to form a good generation. This article discusses Buya Hamka's thoughts on how science relates to religion from an Islamic perspective and how he helped nurture the young generation of Muhammadiyah. This research aims to analyze and deeply analyze Hamka's thoughts related to science and its impact on the formation of a superior Muhammadiyah generation. One of the issues raised by this research is that previous studies have not thoroughly explored Hamka's thoughts and only focused on the historical aspect. Buya Hamka's Personal and Dignity book, along with relevant journals and articles, are used in this research as a qualitative method with a literature study approach. The results show that Hamka saw religion and science as a unity that works together to guide humans towards wisdom and truth. One of Hamka's works, “Falsafah Hidup”, and “Tenggelamnya Kapal Van Der Wijck”, provided inspiration for the Muhammadiyah generation to place science as a pillar of civilization. In short, Buya Hamka's ideas can still be used to address contemporary issues and maintain science-based da'wah.